Heuristics method for truck disassembly process - Yeoh, Kim Hao (2020)
Product recovery is an interesting topic in nowadays especially in remanufacturing industries. Remanufacturers focus on product recovery because of some valuable parts can be used in remanufacturing processes. Disassembly is an important process that extract related valuable parts or subassemblies and materials from discarded products. The discarded products have high degree of uncertainty in the structure and the quality of the returned product. Some parts of the product may cause pollution or may be hazardous. Disassembly Line Balancing Problems (DLBP) is the main issue that remanufacturers have to solve it during disassembly processes. The objectives of this research is to optimize the workstation in a disassembly line and improve the utilization of each workstation by proposed heuristic rule. The Delmia Quest simulation software was used to validate the model between actual disassembly line and proposed heuristic rule. The model proposed apply heuristic rule to create better results compared to actual disassembly line in terms of environmental focus and productivity improvement. Last but not least, the contribution of proposed heuristic rule to remanufacturers is to increase awareness of environmental issues in the disassembly line as well as in the productivity itself. The results showed that by applying the heuristic rule the results are good and improve the hazard and environmental factors.